IgG Subclass Switching In Tumor Infiltrating B Cells and Patient Survival - Nongnapat Kanthakhoo (International Journal of Scientific Research in Science and Technology, 2025)
Tumor infiltrating B cells have been able to be considered as very important in regulation of anti-tumor immunity, but its prognostic role is always context dependent and also not well understood mechanistically. There is a growing amount of evidence to support that clinical outcome is dependent not on evidence of B cell presence, but on the functional quality of intratumoral antibodies. This review summarizes the existing developments on immunoglobulin G (IgG) subclass switching in tumor-infiltrating B cells and discusses its potential use to improve patient survival in solid malignancies. We describe the molecular and microenvironmental(s) that control the process of class-switch recombination in tumors, and the role that chronic exposure to antigens as well as polarization and crosstalk among tumors and immune responses play in determining IgG subclass bias. Specific focus is placed on the opposite actions between cytotoxic and immunosuppressive activities of a series of IgG subclasses, which have been attributed to immune evasion, reduced effects of action target, and poor clinical outcomes. With the data of bulk, single cell and B-cell receptor repertoire analysis we demonstrate how IgG subclass skewing is associated with prognosis and immunotherapy response of immune checkpoint blockade in various cancer types. Lastly we delve into the emergent approaches to therapy trying to reprogram Tumor-infiltrating B cells or trying to harness the biology of the IgG subclasses to promote anti-tumor immunity. Takit together, the present report places IgG subclass switching as the application functioning biomarker and as an encouraging objective of the subsequent-generation immunotherapies in cancer treatment.
Keywords: Tumor-infiltrating B cells; IgG subclass switching; Class-switch recombination; Cancer immunology; Antibody repertoire; IgG4-mediated immunosuppression